Effects of specific badminton training on aerobic and anaerobic capacity, leg strength qualities and agility among college players - Wee, E. H.; Low, J. Y.; Chan, K. Q.; Ler, H. Y. (Sport Science Research and Technology Support, 2019)
Multi-shuttle training was very popular and specific for the badminton training session. The badminton multi-shuttle feeding form possessed the quality of High Intensity Intermittent Training (HIIT) which resulted in physiological adaptations and improvement in physical performance. However, its effectiveness has not been extensively examined in badminton. This study examined the effects of high intensity intermittent badminton multi-shuttle (HIIBMS) feeding training on aerobic and anaerobic capacity, leg strength qualities and agility. Eighteen university college badminton players (AGE = 20 ± 1 year, BW = 65.3 ± 11 kg; H = 173.0 ± 5.3 cm) were recruited into this study. The subjects were pre-tested on aerobic capacity, leg reactive strength, and agility parameters. Subsequently, they were randomly selected and assigned into 2 groups (control group [CG], experimental group [EG]). Both groups had similar badminton training while additional training of HIIBMS feeding training was given to the EG for the duration of 4 weeks. The two groups started equal as the pre-test for the 6 research variables revealed insignificant results. The post-test results were also insignificant for all the 6 variables. However, pre-test and post-test mean scores comparisons showed significant improvements in VO2max, mean power, leg reactive strength and agility except peak power and jump height in EG. CG showed no improvement in all parameters. Further research with longer intervention duration should be conducted to solicit for more information.